Coriolanus - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 2000)
"Coriolanus" by William Shakespeare is a tragedy written between 1605 and 1608. The play follows a proud Roman general who earns his name through military triumph against the Volscians but faces banishment when his contempt for common citizens clashes with political reality. Exiled and embittered, he joins forces with his former enemies to march against Rome itself. When his mother pleads for peace, Coriolanus must choose between vengeance and reconciliation$1 (Ba decision that seals his fate. (This is an automatically generated summary.)s
There is an improved edition of this title, eBook #100
Wikipedia page about this book: https://en.wikipedia.org/wiki/Coriolanus
Release date is 2000-07-01
Keywords: Tragedies (Drama); Generals -- Drama; Rome -- Drama; Coriolanus, Cnaeus Marcius -- Drama